Alterations of Left Ventricle Diastolic Function in Patients with Type 2 Diabetes and its Relationship with Glycated Hemoglobin - جحجاح أكرم; المرعي منيف; عبد طرفة (Latakia University Journal -Medical Sciences Series, 2021)
Objective: Highlight the role of HBA1c as an index for the development of diabetic cardiomyopathy. Methods and patients: in this case-control study, a total of 80 patients with type2 diabetes aged between 40-70 years, were selected from Tishreen University Hospital and been included in the case group and been compared with 80 non diabetic participants as a control group, the two groups were matched in terms of: age, gender, blood pressure and body mass index (BMI), the two groups were scrutinized for Doppler echocardiography, ECG and Blood pressure measurement ,both groups underwent an objective exam, basic biochemistry profile (urea, creatinine, fasting blood glucose, complete blood count). HBA1c analysis was performed for the case group. Results: in the case group Diastolic dysfunction of left ventricle was observed in 66 patients out of 80 (82.5%), the grades of Diastolic dysfunction were 33(50%) for grade I, 22(33.3%) for grade II, 11(16.7%) for grade III, 16(20%) patients of the case group had HBA1c <7,19(23.75%) with HBA1c between 7.1-8, 11(13.75%) with HBA1c between 8.1-9, 20(25%) with HBA1c >9, and 14(17.5%) without diastolic dysfunction all of them had HBA1c <7. in the control group Diastolic dysfunction of left ventricle was observed in 30 participants out of 80 (37.5%), the grades of Diastolic dysfunction grades were 28(93.3%) for grade I, 2 (6.7%) for grade II, 0% for grade III. Conclusions: Diastolic dysfunction of left ventricle is a common finding in patients with type 2 diabetes; HBA1c is reliable index for the risk of developing Diabetic cardiomyopathy with multiple mechanisms.